The role of epigenetic methylation/demethylation in the regulation of retinal photoreceptors - Lu, Chao-Fan; Zhou, Ya-Nan; Zhang, Jingjing; Su, Songxue; Liu, Yupeng; Peng, Guang-Hua; Zang, Weidong; Cao, Jing (Frontiers in Cell and Developmental Biology, 2023)
Photoreceptors are integral and crucial for the retina, as they convert light into electrical signals. Epigenetics plays a vital role in determining the precise expression of genetic information in space and time during the development and maturation of photoreceptors, cell differentiation, degeneration, death, and various pathological processes. Epigenetic regulation has three main manifestations: histone modification, DNA methylation, and RNA-based mechanisms, where methylation is involved in two regulatory mechanisms-histone methylation and DNA methylation. DNA methylation is the most studied form of epigenetic modification, while histone methylation is a relatively stable regulatory mechanism. Evidence suggests that normal methylation regulation is essential for the growth and development of photoreceptors and the maintenance of their functions, while abnormal methylation can lead to many pathological forms of photoreceptors. However, the role of methylation/demethylation in regulating retinal photoreceptors remains unclear. Therefore, this study aims to review the role of methylation/demethylation in regulating photoreceptors in various physiological and pathological situations and discuss the underlying mechanisms involved. Given the critical role of epigenetic regulation in gene expression and cellular differentiation, investigating the specific molecular mechanisms underlying these processes in photoreceptors may provide valuable insights into the pathogenesis of retinal diseases. Moreover, understanding these mechanisms could lead to the development of novel therapies that target the epigenetic machinery, thereby promoting the maintenance of retinal function throughout an individual’s lifespan.